Preliminary results of in vitro fertilization for the endangered murciano-levantina bovine breed (Orinoquia, 2004)
ASBTRACT: The Murciano-levantina  cattle from the Spanish South-East belongs to a  bovine endangered breed under the special protection of FAO (WWL-DAD:3)*. Their characteristics of rusticity,  longe- vity, docility and disease resistance make interesting the recovery of the breed. The objective of the present work   was   to   deter mine   the efficiency of in vitro bovine embryo production using oocytes collected from post mortem ovaries fertilized with frozen thaw sperm obtained either from commercial or Murciano-levantina bulls. Cumulus oocyte complexes were matured for 24 h in TCM199 with 10% FBS, 2mM L-glutamine, 0.2 mM sodium pyruvate, 0.3  µg/mL LH and µg/mL FSH. Oocytes presumed matured  were fertilized with   Percoll-prepared   sper m (750.000/mL) in IVF-TALP as described by Parrish  et al. (Biol. Reprod  38:1171-1180, 1988). Zygotes (at 18 h) or two-cell stage embryos (at  48  h) were assessed by staining  with Hoechst 33342 (µg/mL; 20 min) under an epifluorescence microscopy. The experiment  was replicated  on 4 occasions.The results  of penetration  (PEN-%), average number of spermato- zoa inside the oocyte (S/O), monos permy (MON- %) putative embryos  (zygotes with two pronuclei, 2 PN-%) and percentages of cleavage at 48 hours (Table 1) were recorded. The results show that early embryos can be obtained with no difference with the source of sperm used in the monospermy and the cleavage rate between commercial and Mur- ciano-levantina  sperm (p>0.05). *Lista Mundial de Vigilancia para la Diversidad de los Animales Do- mésticos (1997). http:// www.fao.org/docrep/V8300S/ V8300S00.htm